Off‐Pump to On‐Pump Emergency Conversion: Incidence, Risk Factors, and Impact on Short‐ and Long‐Term Results. Issue 10 (2nd September 2015) - Maroto Castellanos, Luis C.; Carnero, Manuel; Cobiella, Francisco J.; Alswies, Ali; Ayaon, Ali; Reguillo, Fernando J.; García, Mónica
ABSTRACT Background and aim of the study Emergency conversion to on‐pump during off‐pump coronary artery bypass surgery (CABG) increases morbidity and mortality. We analyze its risk factors and impact on short‐ and long‐term outcomes. Methods All patients undergoing isolated CABG between 2006 and 2012 were included. Postoperative and midterm mortality and the combined event (death, myocardial infarction, cerebrovascular accident, and repeat revascularization) were compared between patients with and without conversion. Multivariate analysis and propensity score matching were performed. Results A total of 1268 patients were operated off pump and 37 patients required an emergency conversion. Postoperative death and combined event were more frequent among patients who were converted (31.6% vs. 3.31%, p < 0.001 and 43.2% vs. 11.5%, p < 0.001, respectively). Conversion was an independent predictor of both events (OR = 6.22, 95%CI: 2.01 to 19.3 and OR = 5.06, 95%CI: 2.41 to 10.61, respectively). Mean follow‐up was 32.5 months. At four years, survival and freedom from the combined event was poorer for conversion (75% vs. 88%, p < 0.001 and 50% vs. 79%, p < 0.001, respectively). Conversion was an independent predictor for late mortality (HR = 2.4, 95%CI: 1.1 to 5.22) and the risk of combined event (HR = 2.97, 95%CI: 1.79 to 4.91). A 3:1 propensity score matching analysis was performed: conversion increased both perioperative and four‐year mortality (12.6% vs. 4.5%, p < 0.001 and 25% vs. 12%, p = 0.007); and early and late incidence of the combined event (43.2% vs. 11.7%, p < 0.001 and 53% vs. 24%, p = 0.001). Preoperative atrial fibrillation and previous percutaneous coronary intervention were independent predictors of conversion. Conclusions Emergency conversion from off‐ to on‐pump CABG dramatically worsens early and late outcomes. Previous percutaneous coronary intervention and atrial fibrillation increase the risk of conversion. doi: 10.1111/jocs.12614 (J Card Surg 2015;30:735–745)